Quantitative N-glycoproteomic analysis reveals glycosylation signatures of plasma immunoglobulin G in systemic sclerosis - Cheng, Lu; Li, Yanhong; Zhou, Yu; Ling, Yingying; Wu, Tong; Liang, Zongan; Wu, Yinlan; Tan, Chunyu; Liu, Yi; Zhang, Yong (Frontiers in Immunology, 2025)
Systemic sclerosis (SSc) is a perplexing autoimmune disorder, characterized by mysterious causes, high mortality rates, and a lack of effective treatments. The role of abnormal glycosylation in the onset of autoimmune diseases has been recognized for some time. Nonetheless, the intricate details of intact glycopeptides in SSc remain elusive owing to challenges in their detection. In this study, we characterized plasma immunoglobulin G (IgG) intact N-glycopeptides from 30 SSc patients and 30 healthy controls (HCs) via our recently developed intact glycopeptide analysis method GlycoQuant. Through this approach, twelve differentially expressed intact N-glycopeptides were identified. The correlation of specific intact N-glycopeptides with the clinical features of SSc patients was analyzed. The results revealed a notable increase in the levels of 6 intact N-glycopeptides (IgG2-N3H3F1, IgG2-N3H4F1, IgG2-N4H4F1, IgG2-N4H5F1, IgG2-N5H4F1, and IgG2-N5H5F1) and a decrease in the levels of another set of 6 intact N-glycopeptides (IgG1-N4H3F1, IgG2-N3H6F1A1, IgG2-N4H4F1A1, IgG2-N5H3F1, IgG3-N4H3F1, and IgG3-N4H4F1). These changes in the levels of intact N-glycopeptides are associated with various aspects of SSc, including diffuse SSc (dSSc), interstitial lung disease (ILD), disease progression, cardiovascular involvement and C-reactive protein in the peripheral blood. In summary, this study offers a detailed overview of the intact N-glycopeptide profile in the peripheral blood of patients with SSc, providing valuable insights that could propel further research into SSc.